PROJECT ACTIVITIES IN PRESCHOOL EDUCATION INSTITUTIONS: HEALTH PROMOTION ISSUES - Пономаренко, Тетяна; Науменко, Марина (SWorldJournal, 2024)
The article considers the issues of health protection of children in preschool educational institutions (PEI) in the conditions of a full-scale wa;, notes the need to apply a trauma-informed approach to the organisation of the educational process in PEI,